Adiponectin Prevents Reduction of Lipid‐Induced Mitochondrial Biogenesis via AMPK/ACC2 Pathway in Chicken Adipocyte. Issue 6 (June 2015) - Gan, Lu; Yan, Jun; Liu, Zhenjiang; Feng, Min; Sun, Chao
ABSTRACT Adiponectin (APN) stimulates mitochondrial biogenesis and reduces lipid content in human and animal adipocytes. However, the mechanism of adiponectin in regulating mitochondrial biogenesis in chicken adipocytes has never been reported. The objective of this study is to examine the mechanism that adiponectin plays in lipid‐induced mitochondrial biogenesis and mitochondrial function in chicken adipocytes. We found that the overexpression of adiponectin reduced the membrane DAG content and elevated the membrane translocation of PKCθ. In contrast to control groups, the overexpression of adiponectin increased mitochondrial density and mitochondrial DNA contents and peroxisome proliferator‐activated receptor αcoactivator 1α (PGC1‐α) expression. Mitochondrial membrane potential and cytochrome C (Cyt C) content were detected by JC‐1 fluorescent staining and immunofluorescence which indicated that overexpression of adiponectin enhanced mitochondrial ATP synthesis. Moreover, AMPK/ACC2 signaling pathway was activated along with the elevation of PGC1‐α and TFAM by the overexpression of adiponectin, meanwhile the lipid transcription marker genes were down‐regulated. This effect was alleviated by reducing adiponectin and a specific inhibitor of AMPK pathway. We concluded that adiponectin could prevent reduction of lipid‐induced mitochondrial biogenesis via AMPK/ACC2 pathway in chicken adipocytes. J. Cell. Biochem. 116: 1090–1100, 2015. © 2014 Wiley Periodicals, Inc.